Comparative analysis of renal decline rates in microscopic polyangiitis: unveiling the slowly progressive phenotype - Kanako Tsutsumi; Narumichi Iwamura; Katsumi Eguchi; Ayuko Takatani; Tomohiro Koga; Takeshi Araki; Toshiyuki Aramaki; Kaoru Terada; Yukitaka Ueki (Immunological Medicine)
Although rapidly progressive glomerulonephritis (RPGN) is the main renal phenotype of microscopic polyangiitis (MPA), we aim to clarify the clinical features of slowly progressive MPA. This retrospective observational study included 12 patients diagnosed with MPA in our hospital between January 2012 and February 2022. We investigated the differences in surrogate markers, rate of decline of estimated glomerular filtration rate (eGFR) between the slowly progressive and rapidly progressive MPA groups. Of the 12 patients with MPA, 3 (25.0%) had slowly progressive MPA: MPA within 30% decrease in eGFR 3 months pretreatment, all of whom developed RPGN during the course. Patients with slowly progressive MPA had lower levels of C-reactive protein, myeloperoxidase anti-neutrophil cytoplasmic antibodies, and interleukin-6; higher levels of sialylated carbohydrate antigen KL-6. Slowly progressive MPA is not uncommon in our hospital. A linear relationship was found between slower rate of eGFR decline and lower surrogate markers of disease activity. Some MPA cases have slowly progressive glomerulonephritis leading to RPGN, which may be clinically characterized by low disease activity. It may be useful to measure myeloperoxidase anti-neutrophil cytoplasmic antibody in chronic kidney disease with concomitant urinary abnormalities to diagnose MPA with slowly progressive glomerulonephritis.